Avaliação do Potencial para Ensilagem de Cultivares de Alfafa (Medicago sativa L.) - Monteiro, ALG; Costa, Ciniro [UNESP]; Arrigoni, M. D. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
The objective of this trial was to study the ensilage potential of alfalfa (Medicago sativa L,.). The material used in the evaluation was harvested from an experiment in a complete randomized blocks design with three replicates, with seventeen alfalfa cultivars, Criouil, Florida 77, P555, P581, Moapa, Gilboa, 34 Linea, C/W 8754, C/W 4468, C/W 86, C/W 8746, Hunter Field, Trifecta, Sequel, CUF 101, Aurora e Siriver, during three years. The harvest used for the determinations was collected at 30(th) day of plants development and the material was submitted to two treatments: no wilting - Fresh alfalfa frozen immediately after harvest; wilting fresh alfalfa exposed to sun by three hours to get 35% DM. The dry matter content (DM), water soluble carbohydrates (WSC) and buffer capacity (BC) were evaluated in rhp forages Wilting increased the dry matter content (39,98%), however there were not differences among cultivars. The same occurred for the WSC content, with interaction among cultivars and treatments. The alfalfa cultivars, when submitted to effective wilting practice, presented appropriated characteristics of dry matter and water-soluble carbohydrates for ensilage. Wilting had no effect on alfalfa buffer capacity.
Evaluation of ensilage potential of alfalfa cultivars (Medicago sativa L.)
Keywords: water-soluble carbohydrates; alfalfa silage; alfalfa buffer capacity